The Forest Supply Chain Management: An Entropic Perspective - Tarik Saikouk; Ismail Badraoui; Alain Spalanzani (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
The Supply Chain (SC) represents a complex and dynamic open system characterized by a dissipative structure and positive entropy (Wang, 2008). To better understand the SC dynamic behavior, we present in this paper a conceptual framework to explain how the SC complexity can decrease the operational performance and the value-added creation. A review of the literature shows that the SC positive entropy is a source of its inherent unnecessary uncertainty and its underperformance. Indeed, the non-linear interactions between the SC actors and their incapacity to share relevant information represent a source of several entropic behaviors. To reach our research objective, and after presenting the literature review of the SC complexity, we show that the incapacity to share relevant information and the ineffective traceability information management can represent a SC positive entropy amplification source. Then, we highlight how a traceability system and automatic information sharing process can reduce the Wood SC information dissipation and improve the wood allocation. After that, we use empirical results from the European project "Indisputable Key" to highlight how Radio Frequency IDentification (RFID) traceability system can create "negative entropy" in the Wood SC, and improve the wood allocation by quickly allowing companies to access relevant wood information. Since the forest-wood sector is a low economical margin sector; any wood allocation improvement would be a source of added value and a competitive lever for companies.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; supply chain system; entropy-negentropy; traceability system; forest supply chain; french case